Solvent solutions: comparing extraction methods for edible oils and proteins in a changing regulatory landscape. Part 1: Physical-properties☆ - Carré Patrick; Berthold Sebastian; Piofczyk Thomas; Bothe Sarah; Hadjiali Sara (Oilseeds and fats, crops and lipids)
In the context of potential regulatory changes, this study compares the properties of various solvents for the extraction of edible oils. The solvents considered are hexane isomers, alcohols, ketones, ethyl acetate, dichloromethane and 2-methyloxolane. The study presents a detailed table of physical properties for each solvent, including boiling point, density, vapour pressure, flash point and miscibility with water. It also addresses chemical stability, reactivity and potential interactions of these solvents with oilseeds. Particular attention is given to solvent-substrate interactions measured by Hansen solubility parameter. Normal hexane and its isomers show high affinity for neutral lipids, a lesser one for polar lipids and fair selectivity for non-lipids. Due to their hydroxyl group, alcohols (methanol, ethanol, isopropanol) exhibit only a modest affinity for non-polar lipids, though this affinity increases with the number of carbon atoms in the alcohol molecule. They demonstrate a higher efficacy in extracting polar lipids; however, this extraction process also extends to numerous non-lipidic molecules. Ketones (acetone, MEK) offer a balance, with theoretically good affinity for both polar and non-polar lipids, although in practice they do not dissolve phospholipids. Ethyl acetate shows good solvent power for various lipids, its ester group being found in most of lipid molecules. Dichloromethane is a good solvent for lipids in general but raises potential safety concerns. 2-Methyloxolane is noted for its ability to efficiently extract both polar and non-polar lipids, offering a potential compromise between hexane-like and more polar solvents however, it is potentially hindered by its price and its limited availability.